2021
DOI: 10.1002/essoar.10508117.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ensemble-Based Assimilation of Satellite All-Sky Microwave Radiances Improves Intensity and Rainfall Predictions for Hurricane Harvey (2017)

Abstract: Tropical cyclones (TCs; see Appendix A for a list of acronyms) are among the most devastating natural disasters in the tropics and mid-latitudes. They make for a triple-threat of wind damage, surge inundation, and inland/freshwater flooding, the last of which is a leading cause of fatalities in the United States from TCs (Rappaport, 2014). Accurate predictions of TCs are valuable to society because they facilitate targeted and efficient preparations for mitigating the loss of life and property.While forecasts … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…If the model ALWC pattern at the initialization time matches that in observations, then a forecaster may have higher confidence in that HWRF forecast. It is also consistent with recent modeling studies which assimilated all‐sky radiance from microwave satellite measurements to improve the performance of model simulations (Minamide & Zhang, 2018; Zhang, Gopalakrishnan, 2016; Zhang, Minamide et al., 2016; Zhang, Sieron, et al., 2021; Zhang, Soden, et al., 2021). Overall, this study supports previous modeling and observational studies which suggested that radiative heating plays a critical role in bolstering TC intensification.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…If the model ALWC pattern at the initialization time matches that in observations, then a forecaster may have higher confidence in that HWRF forecast. It is also consistent with recent modeling studies which assimilated all‐sky radiance from microwave satellite measurements to improve the performance of model simulations (Minamide & Zhang, 2018; Zhang, Gopalakrishnan, 2016; Zhang, Minamide et al., 2016; Zhang, Sieron, et al., 2021; Zhang, Soden, et al., 2021). Overall, this study supports previous modeling and observational studies which suggested that radiative heating plays a critical role in bolstering TC intensification.…”
Section: Discussionsupporting
confidence: 88%
“…Recent modeling studies have demonstrated the importance of radiative processes on TC development, particularly at the early stages of development where radiative heating makes up a larger fraction of the total diabatic heating within a storm. In model simulations, suppressing radiative interactions acts to slow or inhibit tropical cyclogenesis, highlighting the potential importance of radiative heating on TC development (Bretherton et al., 2005; Bu et al., 2014; Carstens & Wing, 2020; Fovell et al., 2016; Melhauser & Zhang, 2014; Muller & Romps, 2018; Smith et al., 2020; Wing et al., 2016; Zhang, Soden, et al., 2021; Zhang, Sieron, et al., 2021). Also, the modification in radiative forcing in full‐physics numerical simulations influences the evolution of TC wind fields (Fovell et al., 2016; Melhauser & Zhang, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides expanding on validations, another important avenue of future work is to improve TMeCSR by including more observations. At the time of writing, the microwave DA capability in the PSU‐EnKF is under development (Y. Zhang et al., 2021). From the experiences of operational forecasting, the assimilation of space‐borne microwave radiometer data from sounding channels is likely to improve the quality of the TMeCSR data set (Geer et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the radiance data, from microwave sounder [the Advanced Microwave Sounding Unit‐A (AMSU‐A) and the Advanced Technology Microwave Sounder (ATMS)], microwave imager [Advanced Microwave Scanning Radiometer 2 (AMSR2), Global Precipitation Measurement (GPM) Microwave Imager (GMI) and Special Sensor Microwave Imager/Sounder (SSMIS)] and humidity sounder [Microwave Humidity Sounder (MHS) and GMI], are capable of providing thermodynamic information under the all‐sky condition. A better description of the tropical cyclone thermodynamic fields under the all‐sky condition allows for reasonable deep convective triggering and development, thus leading to an improved representation of rapid intensification through the assimilation cycle (Kazumori & Kadowaki, 2017; Tong et al., 2020; Zhang et al., 2021). In addition to these impacts, all‐sky MW radiance assimilation also improves the tropospheric wind fields, resulting in better midlatitude atmospheric circulation and improves TC track prediction (Xian et al., 2019; Yang et al., 2016; Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%